The Effect of Topical Glutathione on Malondialdehyde Levels in Rat with Cataract-Induced Sodium Selenite - Oknita Lasmaini; Muhammad Hidayat; Rinda Wati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Oxidative damage plays a key role in the lens opacity process. Reducing glutathione (GSH) is a tripeptide protein capable of preventing the accumulation of dangerous levels of oxidation products such as hydrogen peroxide and protein disulfide bonds. Human cataract lenses contain reduced levels of reduced glutathione, so by maintaining high levels of reduced glutathione in vivo, it may be possible to prevent opacification of the lens. This study aimed to determine the effect of topical glutathione on sodium selenite-induced cataracts based on the MDA level of the rat lens. Methods: This was an experimental study using 30 rats grouped into 3 groups (K+, P1, and P2). At the end of the study, the lens was dripped with Mydriaticum, then assessed for lens opacity. The more opacity lens was extracted, and subsequently, malondialdehyde level was measured. MDA level was analyzed using the One Way ANOVA test. Results: The average values of rat MDA Lens levels in the K+, P1, and P2 groups were 1.91, 1.38, and 1.2 nmol/mL. Statistically, there was a significant difference in MDA levels in each treatment group with p = 0.001 (p <0.05). Analysis of the average difference in MDA between each group showed that the average MDA level of rats in the P2 group was lower than P1, the MDA levels in the P1 and P2 groups were lower than K+, and there were statistically and clinically significant differences. Conclusion: Topical glutathione can effectively reduce the progression of cataracts in the lens of rats induced by sodium selenite which is identical to senile cataracts in humans in its mechanism of oxidative stress.